Self-Efficacy and Alexithymia as Moderators between Perceived Social Support and Stress among Parents of Children with Learning Disabilities - Abbasi, Mohammad (European Journal of Mental Health, 2017)
The purpose of this cross-sectional study was to examine Self-Efficacy and Alexithymia as moderators between perceived social support and Stress among parents of children with Learning Disabilities. The convenience sample of the study consisted of 98 parents of children with Learning Disabilities from Ahwaz (Iran). This descriptive correlational study was conducted in 2014-15. Multidimensional Scale of Perceived Social Support (MSPSS), General Self-Efficacy Scale (GCE), Toronto Alexithymia Scale (TAS-20), and Perceived Stress Scale (PSS) were completed by parents. Hierarchical linear regression analyses were used to examine the moderating role of Self-Efficacy and Alexithymia. The results revealed that Self-Efficacy and Alexithymia were moderators in the relationship between Perceived social support and Stress. The findings supported the hypothesis that higher levels of self-efficacy (see: Figure 1) would be associated with lower levels of Stress, and that lower levels of Alexithymia (see: Figure 2) would be associated with lower levels of Stress.